Professional Competencies Learned Through Working on a Medication Education Project - Hämeen-Anttila, Katri (American Journal of Pharmaceutical Education, 2010)
OBJECTIVES: To implement a medication education project and assess the competencies students learned and implemented in professional practice after graduation. DESIGN: Fourth-year pharmacy students planned, carried out, and reported on a real-life project during 1 study year. Outside experts and 2 faculty members facilitated the work. The aim of the medication education project was to create material that schoolteachers could use to teach children about rational use of medicines. ASSESSMENT: All students who had participated in the medication education program during its 3 years were contacted (n = 31). A questionnaire was sent to the 21 students who had graduated (18 responded), and a focus group was conducted with the 10 students completing their final year of pharmacy school (9 participants). The competencies that the students reported learning most were teamwork and social interaction skills. They considered the project motivating but also found it challenging and the deadlines frustrating. CONCLUSIONS: Through participation in a medication education project, students learned interpersonal skills, time management, conflict resolution, and other skills that many of them already were finding valuable in their professional practice.